The Determinants of Banks’ Liquidity in Vietnam - Le, Tam; Nguyen Anh, Tu (VNU Journal of Science: Policy and Management Studies, 2017)
This paper is aimed to identify the key determinants of commercial banks’ liquidity in Vietnam, testing the hypotheses of trade-off between bank liquidity and profitability. The random effect model (REM) is applied with data of 140 observations from 20 Vietnamese commercial banks in period 2008 to 2014. The key findings are: First, there is no trade-off between liquidity and profitability, as banks have better profitability will pay more attention to keeping liquidity in safe level. Second, interest rate policy has good and positive impact on bank liquidity, implying the importance of discount window and open market operation in providing liquidity to commercial banks. Third, however, opportunity cost of keeping liquid assets has negative impact on banks’ liquidity, which means that liquidity buffer should reflect the opportunity cost of keeping liquid assets instead of loans. Fourth, bank size is negatively related with banks’ liquidity, which means that smaller banks are more concerned about the liquidity problems than big banks. This is the signal for Vietnamese policy makers to start avoiding the “too big to fail” problem when restructuring the banking system and the plan for increasing the bank size to regional and international levels. Lastly, GDP growth has negative impact on banks’ liquidity. The better is the economic investment opportunities, the less the chance for banks to keep more liquidity. Customers will request more debts, while the demand of ithdrawing cash from banks will be lower. Therefore, managing bank liquidity in Vietnam needs to pay attention to these characteristics. Key words: bank liquidity, determinants, liquid assets, opportunity cost, profitability.